2014
DOI: 10.1179/1743132814y.0000000423
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence of temozolomide and bevacizumab in treatment of gliomas

Abstract: Our collected data support the addition of radiotherapy, BEV, and other targeted agents to TMZ treatment, indicating prolonged survival duration in newly diagnosed patients. However, the optimal regimen for treating high-grade glioma cannot be concluded without more clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 115 publications
0
41
0
Order By: Relevance
“…Among the antiangiogenic drugs, bevacizumab (Avastin™; Genentech, CA, USA) is a monoclonal antibody that targets vascular endothelial growth factor [110]. Preclinical studies with ferumoxytol have shown reduction in rCBV values [101,102] and decreased permeability [102] in tumors following bevacizumab treatment.…”
Section: Imaging Treatment Effects and Therapy Monitoringmentioning
confidence: 98%
“…Among the antiangiogenic drugs, bevacizumab (Avastin™; Genentech, CA, USA) is a monoclonal antibody that targets vascular endothelial growth factor [110]. Preclinical studies with ferumoxytol have shown reduction in rCBV values [101,102] and decreased permeability [102] in tumors following bevacizumab treatment.…”
Section: Imaging Treatment Effects and Therapy Monitoringmentioning
confidence: 98%
“…The tumors invariably recur, 90% of them at the original site, and therapeutic strategies in recurrent tumors are controversial. [13][14][15] Other types of brain tumors include extra-axial meningiomas (w30%), and a rare but distinctive kind is primary CNS lymphomas (PCNSL). 8,16 However, the bulk of literature on FDG-PET in primary brain tumors is on gliomas, which also is the focus of this article.…”
Section: Basics Of Primary Brain Tumorsmentioning
confidence: 99%
“…Current standard glioma therapy involves surgical removal of tumor tissue followed by radiotherapy or chemotherapy (Pérez López & Otero Hernández, ). Tumor tissue removal by surgery is the best option in glioma therapy, but its feasibility depends on the tumor position in the brain (Nanegrungsunk, Onchan, Chattipakorn, & Chattipakorn, ). Although complete removal or debulking of the tumor tissue results in better prognosis by reducing the tumor volume and histological diagnosis (Taal, Bromberg, & van den Bent, ), it also includes the chances of recurrent tumor development at the original site or the distant site.…”
Section: Current Management Of Gliomamentioning
confidence: 99%
“…Although complete removal or debulking of the tumor tissue results in better prognosis by reducing the tumor volume and histological diagnosis (Taal, Bromberg, & van den Bent, ), it also includes the chances of recurrent tumor development at the original site or the distant site. Therefore, the continuation of adjuvant radiation or chemotherapy is vital to prevent tumor growth (Nanegrungsunk et al, ). Radiation includes many complications such as necrosis of brain tissues, cognitive impairment, and secondary tumor.…”
Section: Current Management Of Gliomamentioning
confidence: 99%
See 1 more Smart Citation